Internalisasi Nilai-Nilai Islam Melalui Bimbingan dan Konseling dalam Pembentukan Kemandirian Anak Tunagrahita di SLBN 1 Yogyakarta - Nailan Hivatia; Nurjannah Nurjannah (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
Developing independence among children with intellectual disabilities requires educational approaches that integrate practical life skills with character and spiritual development. This study examines how Islamic values are internalized through Islamic Guidance and Counseling within culinary vocational activities at SLBN 1 Yogyakarta. A qualitative design with a narrative approach was employed, with data collected through observations, semi-structured interviews, and documentation involving guidance and counseling teachers, culinary instructors, and students with intellectual disabilities. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the internalization of Islamic values is implemented through continuous guidance, behavioral habituation, role modeling, motivational support, and spiritual reinforcement during culinary learning activities, fostering discipline, responsibility, self-confidence, social interaction, and simple vocational competencies that contribute to students' independence. Overall, the study demonstrates that integrating Islamic Guidance and Counseling with vocational education creates a holistic learning environment that effectively supports both character formation and the development of adaptive life skills for children with intellectual disabilities in special education settings.